2022
DOI: 10.21203/rs.3.rs-2119853/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microgravity Induces Interplay Between Atg8, Tua and Tub Gene Expression in Arabidopsis Thaliana

Abstract: Autophagy plays a direct or indirect roles in plant growth and development, pathogen invasion and immunity. It is involved in the control of cell homeostasis and modulates plant response and adaptation to various abiotic stress stimuli. The formation and motility of autophagosomes require microtubule dynamics. The manner in which autophagy can be induced by microgravity in plants has not been previously studied. Investigating how plants can cope with the absence of gravity is a critical task in space biology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…As a result of the analysis of the expression of 6 αand 9 β-tubulin genes, an increase in the expression levels of tua2, tua3, tua4, tua6 genes and a decrease in expression of tua4, tua5 genes on the 6 th and 9 th days of cultivation were found (Table 1). On the 12 th day of plant growing under clinostating conditions, none of the six studied genes showed an increase in the level of expression (Table 1) [25]. The tua1 gene is probably not involved in autophagy, as its expression level was consistently low during long-term cultivation.…”
Section: Results Of Research and Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…As a result of the analysis of the expression of 6 αand 9 β-tubulin genes, an increase in the expression levels of tua2, tua3, tua4, tua6 genes and a decrease in expression of tua4, tua5 genes on the 6 th and 9 th days of cultivation were found (Table 1). On the 12 th day of plant growing under clinostating conditions, none of the six studied genes showed an increase in the level of expression (Table 1) [25]. The tua1 gene is probably not involved in autophagy, as its expression level was consistently low during long-term cultivation.…”
Section: Results Of Research and Discussionmentioning
confidence: 96%
“…Analysis of root apex tissues using two autophagosome markers -monodansyl cadaverine and Lyso-Tracker™ Red -showed that the density of autophagosomes in the root apices of clinostated plants was significantly higher than in the control [24,25,28]. The dynamic of the formation of autophagosomes in the root tissues of control and experimental plants was different.…”
Section: Results Of Research and Discussionmentioning
confidence: 99%
See 2 more Smart Citations